The Sony walkman (2000)
Why a design classic is a design classic? Is a question that has to be approached from different ways in order to make all the components, put them together and, finally, build the answer. To study a design classic one should at least explore about it´s history, what was the need that has to be fulfilled at that moment, which was the role of technology in the first stages of development, was it a new product or an improvement of an existing one? which was the design policy of the manufacturer?, what was the context of the design decisions?, explore the evolution of the actual design, how was and how it is marketed?, and, finally, what uses and meanings it generated and continues generating in the present moment?.